2010
DOI: 10.1182/blood-2009-08-237586
|View full text |Cite
|
Sign up to set email alerts
|

Putative GTPase GIMAP1 is critical for the development of mature B and T lymphocytes

Abstract: The guanosine triphosphatases (GTPases) of the immunity-associated protein (GIMAP) family of putative GTPases has been implicated in the regulation of T-lymphocyte development and survival. A mouse conditional knockout allele was generated for the immune GTPase gene

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
81
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 57 publications
(86 citation statements)
references
References 45 publications
4
81
0
1
Order By: Relevance
“…Of significance to the present discussion, recent work in one of our laboratories has demonstrated that GIMAP1, like GIMAP5, is required for the protection of lymphocytes against cell death. 21 Together these data imply that GIMAP proteins are required in different organelles to provide protection against cell death. A mechanistic explanation of these phenomena will therefore need to encompass events in both (endo)-lysosomes and the Golgi apparatus.…”
Section: Gimap5mentioning
confidence: 95%
“…Of significance to the present discussion, recent work in one of our laboratories has demonstrated that GIMAP1, like GIMAP5, is required for the protection of lymphocytes against cell death. 21 Together these data imply that GIMAP proteins are required in different organelles to provide protection against cell death. A mechanistic explanation of these phenomena will therefore need to encompass events in both (endo)-lysosomes and the Golgi apparatus.…”
Section: Gimap5mentioning
confidence: 95%
“…Interestingly, a total of 16 of 39 genomes (41.0%) revealed loss of chromosomal material comprising the EZH2 and GIMAP locus on chromosome 7q36 (supplemental Figure 4). Although this locus and genes in the GIMAP family have been shown to be important in the regulation of T-lymphocyte development and survival, 33,34 they have not been previously implicated in the pathogenesis of T-PLL. Our CNV analysis suggests that the function of these genes is important in regulation of T-cell proliferation and can be deregulated in malignancy.…”
Section: Cnv Analysis Confirms Abnormalities Involving the Atm Locusmentioning
confidence: 99%
“…Mutations in this gene have been linked to susceptibility to recurrent viral infections (36). GIMAP1, GTPase IMAP family member 1, is thought to be involved in the differentiation of inflammatory T helper (Th) cells of the Th1 lineage (37,38). CISH belongs to the cytokine-induced STAT inhibitor (CIS) family, also known as suppressor of cytokine signaling (SOCS) protein family, known to be cytokine-inducible negative regulators of cytokine signaling (39).…”
Section: Microarray Analysis Of Human Nk Cells Stimulated By Gal-9mentioning
confidence: 99%